Pengaruh Variabel Fundamental terhadap Struktur Modal (Studi pada Perusahaan Makanan dan Minuman yang Go-Public di Indonesia) - Siti Rahmah; Ardi Paminto; Irsan Tricahyadinata (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study discussed the Influence of Fundamental Variables which measured by Basic Earning Power, Firm Size, Fixed Asset Ratio, and Non-Debt Tax Shield against Capital Structure as measured by Debt to Equity Ratio in Food and Beverage Company that listed in Indonesia Stock Exchange in 2012- 2014. The data used in this research is secondary data obtained from the official website of the Indonesian’s Stock Exchange. The analytical method used in this research is Multiple Regression Analysis, Classical Assumption Test (Test Normality, Test Autocorrelation, Test Heterocedastity, and Test Multicollinearity) and Hypothesis Testing (Test The coefficient of determination or R2 and Test Partial or T-test) using SPSS version 21. The selection of the sample procedure is by using purposive sampling with samples that meet the criteria of 11 companies. Based on the results obtained by analysis of partial that the independent variables Basic Earning Power has a significant negative effect on Debt to Equity Ratio, where Fixed Asset Ratio has a significant positive effect Debt to Equity Ratio, also Firm Size and Non-Debt Tax Shield has a positive effect was not significant to the Debt to Equity Ratio on Food and Beverage at the Indonesia Stock ExchangeKeywords: Basic Earning Power, Firm Size, Fixed Asset Ratio, and Non-Debt Tax Shield, Debt to Equity Ratio.